Pengembangan Sistem Informasi Tender Management Project untuk Optimalisasi Pengelolaan Administrasi Paket Lelang - Muhammad Nurfalah Setiawan; Pramudya Prima Insan Prayitno; Nasruddin Bin Idris (Jurnal Ilmiah Matrik, 2026)
The management of tender package administration involves handling project data, documents, and reporting activities. In practice, these processes are often performed using spreadsheets and email-based data exchange, which may lead to issues such as data redundancy, delayed updates, and limited capability for centralized monitoring. In addition, the absence of an integrated system for reporting project activities reduces the effectiveness of information delivery to management. This study aims to develop a Tender Management Project Information System to support integrated administration of tender packages. The research adopts a qualitative descriptive approach, with data collected through observation, interviews, and literature review. The system is developed using the Rapid Application Development (RAD) method, which includes requirement planning, system design, development, and implementation phases. System modeling is conducted using Unified Modeling Language (UML), and the application is implemented as a web-based system. The results indicate that the proposed system is capable of managing tender data, organizing documents, and monitoring project progress within a centralized platform. The system also supports role-based user management, enabling more structured data handling and improved administrative efficiency. Therefore, the developed system provides a practical solution to enhance the effectiveness of tender administration processes.